Criterios jurídicos valorativos para priorizar la aplicación de la cadena de custodia en los delitos de feminicidio en Loreto - Mejia Sanchez, Rocio del Pilar (2023)
The present investigation considers that an essential aspect of the judicial process is the Evidence; whose function within Criminal Law is to determine the veracity of the commission of a punishable act, identify the author and aggrieved party. However, it questions the procedure carried out by the intervening parties during the Judicial Investigation in the collection, packaging, transportation, delivery and conservation of the material elements found at the crime scene, until their exposure in the Criminal trial; because these are not simple indications, but proof of judgment, which facilitates the proper administration of Justice and the application of the Criminal Law. For this reason, a mismanagement of the evidence could have negative consequences within the Process. The objective was to establish the evaluative criteria to prioritize the application of the chain of custody in the crimes of femicide in Loreto. For this reason, the exploratory level basic research method oriented to the search for new knowledge was applied; In this way, the principle of utility and relevance was achieved as a result; the principle of conductivity; the principle of legality and the need for legislative reform.